2021
DOI: 10.2478/aoas-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

The Welfare Status of Hens in Different Housing Systems – A Review

Abstract: The currently used poultry farming methods, which aim to maximise economic profit, are based on ever new technological solutions that improve flock management and increase bird performance. However, they do not always meet the natural needs of birds. Every housing method and technological solution currently in use is faced with some issues, such as social stress, adverse temperature/humidity conditions, risk of zoonoses, and behavioural pathologies, which determine poultry performance and welfare. Disregard fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 157 publications
(159 reference statements)
0
11
0
1
Order By: Relevance
“…Body condition score in laying hens of DLS group was better than that of the CON group. Birds with poor feathers not only present a problem for welfare, but also affect egg production (Tactacan et al, 2009;Sosnówka-Czajka et al, 2010;Sözcü et al, 2022). Bad 9.36 ± 0.65 a 0.031 CON -conventional feeding system, DLS -digital livestock system; data are presented as mean value ± SEM (standard error of the mean), n = 15; ab -means within a row with different superscripts are significantly different at P < 0.05 environment and feeding management conditions of laying hens of CON group might have increased feather loss compared to the DLS group, thus impairing animal welfare (Blatchford et al, 2016;Widowski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body condition score in laying hens of DLS group was better than that of the CON group. Birds with poor feathers not only present a problem for welfare, but also affect egg production (Tactacan et al, 2009;Sosnówka-Czajka et al, 2010;Sözcü et al, 2022). Bad 9.36 ± 0.65 a 0.031 CON -conventional feeding system, DLS -digital livestock system; data are presented as mean value ± SEM (standard error of the mean), n = 15; ab -means within a row with different superscripts are significantly different at P < 0.05 environment and feeding management conditions of laying hens of CON group might have increased feather loss compared to the DLS group, thus impairing animal welfare (Blatchford et al, 2016;Widowski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Bad 9.36 ± 0.65 a 0.031 CON -conventional feeding system, DLS -digital livestock system; data are presented as mean value ± SEM (standard error of the mean), n = 15; ab -means within a row with different superscripts are significantly different at P < 0.05 environment and feeding management conditions of laying hens of CON group might have increased feather loss compared to the DLS group, thus impairing animal welfare (Blatchford et al, 2016;Widowski et al, 2017). The high score of feather loss in laying hens of CON group might have contributed to wing feather deterioration (Lay et al, 2011;Sosnówka-Czajka et al, 2010). In this study, appearance, feather condition, body condition such as the comb, beak, keel bone damage, and plumage, and health score of laying hens of the DLS group were improved compared to the CON group.…”
Section: Discussionmentioning
confidence: 99%
“…Contaminated eggs have been a problem in free-range systems. The main factors affecting these results are nest contamination or egg laying on litter [42], [43]. The study [37] reported that the proportion of dirty eggs higher in the free-range system compared to the cage system, especially in the hens' last phase of the production period, could be related to unfavorable rainy weather conditions.…”
Section: Volume 17 267 2023mentioning
confidence: 99%
“…One of the increasingly popular alternatives to battery cage housing system is the aviary housing system. Aviaries are tiered structures that provide nest boxes for laying eggs, perches for perching, elevated areas for roosting, and a litter area for foraging and dustbathing ( Sosnówka-Czajka et al., 2021 ). Accordingly, the use of aviaries is considered beneficial for skeletal development; previous research has found that pullets and laying hens reared in aviaries have stronger bone quality with improved musculoskeletal development compared to those reared in conventional cage systems ( Regmi et al., 2015 , 2017 ; Neijat et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%